2004
DOI: 10.1097/00005721-200407000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a Laboring Women With Amyotrophic Lateral Sclerosis

Abstract: A case presentation of a pregnant 32-year-old woman with advanced amyotrophic lateral sclerosis who presented in labor at 38+6 weeks gestation is described. Amyotrophic lateral sclerosis is a progressive neuromuscular disease that attacks nerve cells in the brain and spinal cord. It is usually diagnosed after the fourth decade of life, and is more commonly seen in men than women; thus, it is rarely found in the obstetric population. When the perinatal team is confronted with a pregnant woman with ALS,patient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…In the 1950s Huston et al [24] reported the occurrence of ALS and pregnancy in 17 women in Guam, where the incidence was approximately 100 times greater than elsewhere, and the disease was found to be predominantly familial. Another 15 cases of ALS in pregnancy have been reported in the medical literature [5][6][7][8][9][10][11][12][13][14][15][16][17]. In one case of apparently sALS, Weiss and co-workers [15] reported an alanine for valine substitution in codon 4 in the SOD1 gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1950s Huston et al [24] reported the occurrence of ALS and pregnancy in 17 women in Guam, where the incidence was approximately 100 times greater than elsewhere, and the disease was found to be predominantly familial. Another 15 cases of ALS in pregnancy have been reported in the medical literature [5][6][7][8][9][10][11][12][13][14][15][16][17]. In one case of apparently sALS, Weiss and co-workers [15] reported an alanine for valine substitution in codon 4 in the SOD1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the remaining 14 patients had a strong family history of ALS, but the genetic aspects of these cases were not investigated [8,10]. The median age at onset of the patients described so far in the literature [5][6][7][8][9][10][11][12][13][14][15][16][17], including our patients with ALS in pregnancy, is 31.5 years (range 21-42 years). This is in contrast with the median older age of patients described in the literature having the sporadic form of the disease [1,25], whereas it is closer to the earlier age of onset observed in the familial form, which may actually coincide with reproductive age [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 La ELA durante el embarazo es poco común, sólo 18 casos se han descrito a nivel mundial. [3][4][5][6][7][8][9][10][11][12][13] En México, es el segundo caso reportado. 14 La serie más grande de esta asociación se describió en la isla de Guam en 1956 con una mayor prevalencia de la variante familiar de la enfermedad.…”
Section: Reporte De Casounclassified